Innovation in direct intrahepatic portosystemic shunt; a developing country experience - Muhammad Misbah Tahir,; Muhammad Ali,; Lubna Kamani,; Tauqeer Shaikh,; Danial Khalid Siddiqui,; Khalid Mustafa, (Journal of the Pakistan Medical Association, 2023)
Anticoagulants are the first-line treatment option for patients with Budd-Chiari syndrome (BCS); however, intervention is required when this fails. Although, the ultimate treatment is liver transplant, other radiological procedures are for the management of the disease and bridge to definitive therapy. TIPS (trans jugular intrahepatic portosystemic shunt) is a method used by interventional radiologists to create a shunt between portal vein and hepatic vein. At times it is technically not possible, in such cases, direct intrahepatic portosystemic shunt (DIPS) is performed. This patient underwent a successful DIPS procedure for BCS along with balloon dilatation (venoplasty) for inferior vena cava (IVC) stenosis. Keywords: Budd-Chiari syndrome (BCS), Trans jugular intrahepatic portosystemic shunt (TIPS), direct intrahepatic portosystemic shunt (DIPS), inferior vena cava (IVC).